Suicide in Mexican Prisons: Mental Health Symptomology and Risk Factors for Suicidal Ideation and Suicidal Behavior - Pérez-Ramírez, Berenice (The prison journal, 2021)
In Mexico, suicide and suicidal behaviors (SB) have increased 275% since 1990. Prisoners constitute a growing population in Mexico and have been identified as high suicide risk. Using a sample of 194 male prisoners, we measure what demographics and mental health symptomology are associated with suicidal ideation (SI) and SB, and identify what demographics and mental health symptomology predict SI and SB. Global Severity and Adverse Childhood Experiences (ACEs) were significant predictors of experiencing SI, whereas global severity, ACEs, and age were significant predictors of experiencing SB. Findings support increased identification and comprehensive mental health services addressing suicidality in prisons.